QT and JT Dispersion in Children With Familial Mediterranean Fever - M. Kürşat FİDANCI and Ayhan KILIÇ and Mustafa GÜLGÜN and Gökalp BAŞBOZKURT and Cengizhan AÇIKEL and Doğan ŞİMŞEK and Faysal GÖK and Erkan DEMİRKAYA (Archives of Rheumatology, 2015)
Objectives: This study aims to determine QT dispersion and JT dispersion, and their relationship with conventional echocardiography values in a group of children with familial Mediterranean fever (FMF). Patients and methods: The study included 48 FMF patients (26 males, 22 females, mean age 11.10±3.42 years; range 5 to 18 years) as the FMF patients and 31 healthy children (17 males, 14 females, mean age 9.61±2.83 years; range 5 to 17 years) as the healthy controls. Electrocardiography and conventional echocardiography were performed on the FMF patients and healthy controls. Both groups were evaluated with a standard 12-lead electrocardiography. QT, JT and RR distances were measured in both groups. The corrected QT (QTc) and corrected JT (JTc) were calculated. QTcd and corrected JT dispersion (JTcd) were detected. Results: There was no statistically significant difference between the FMF patients and healthy controls in terms of RR, QT, QTd, QTcd, JT, JTc, JTd, and JTcd measurements and echocardiography parameters. QTc value was higher in the FMF patients than the healthy controls. Conclusion: QTc value indicates increased ventricular sensitivity and is an important marker of cardiovascular mortality. It has an important effect on sudden cardiac death and arrhythmia. Our study results suggest that electrocardiographic monitoring may be useful in patients with FMF.